An Examination of Climate Change Phenomena in Coastal Areas and Small Islands (Case Study: Mapur Island, Bintan Regency): Kajian Fenomena Perubahan Iklim Pada Wilayah Pesisir Dan Pulau-Pulau Kecil (Pulau Mapur Kabupaten Bintan) - Rio Saputra; Khodijah Ismail; Dony Apdillah (Media Ilmiah Teknik Lingkungan (MITL), 2025)
Climate change has affected the availability of local food on small islands such as Mapur Island in Bintan Regency. Global climate change has become a critical environmental issue worldwide, drawing attention not only in Indonesia but also across other nations. This global phenomenon influences various aspects of life in Indonesia, particularly in small islands and coastal regions such as Bintan Island. To understand the dynamics of climate change on Mapur Island, it is essential to identify the most relevant indicators of climate change. Small islands and coastal areas like Mapur are highly vulnerable to climate change due to their dependence on local natural resources and ecologically sensitive environments. This study aims to analyze the climate changes occurring on Mapur Island. It employs a mixed-methods approach, integrating both quantitative and qualitative methodologies to examine the impact of climate change on the availability of local food in Mapur Island, Bintan Regency. A stratified proportional random sampling technique was used in the data collection process. The findings indicate that Mapur Island has experienced significant fluctuations in weather variables attributable to climate change. Notably, maximum wind speeds demonstrated sharp fluctuations, with pronounced wind surges occurring between late 2020 and early 2021, as well as from 2022 to 2023.